Evaluation of in vitro cytotoxic activity of different solvent extracts of Clerodendrum thomsoniae Balf.f and its active fractions on different cancer cell lines - V. K. Muhammed Ashraf; V. K. Kalaichelvan; V. V. Venkatachalam; R. Ragunathan (SpringerOpen, 2021)
Abstract Background Clerodendrum is a genus of about 500 species belongs to the family Lamiaceae. Many species of this genus have been proved for the treatment of various diseases. This study was aimed to evaluate the cytotoxic effect of different solvents and their most active fractions of Clerodendrum thomsoniae Balf.f. in different human cancer cell lines. Aerial parts of the plant were subjected to Soxhlet extraction. Phytochemical analysis was done by using standard tests. In vitro anti-cancer activity on MCF-7, Hep-G2, A549, HT-29, MOLT-4, Hela, and Vero cell lines were evaluated by MTT assay. Results Phytochemical analysis confirmed the presence of most of the phytoconstituents in ethyl acetate extracts and the same extracts were found to be more cytotoxic activity to cancer cell lines MCF-7,Hep-G2,A549,HT-29, MOLT-4, and Hela with IC50 values 29.43 ± 1.44 μg/ml, 43.22 ± 1.02 μg/ml, 56.93 ± 1.41 μg/ml, 60.68 ± 1.05 μg/ml, 69.83 ± 1.33 μg/ml, and 40.02 ± 1.14 μg/ml respectively, while it had no cytotoxic effect on normal Vero cells IC50 = 367.5 ± 1.03 μg/ml. Ethyl acetate extracts were selected for the fractionation and MCF-7 cell line was used repeat MTT assay and found that fraction F5 was the most active fraction with IC50 17.33 ± 0.54 μg/ml. Conclusion These findings have proved that Clerodendrum thomsoniae Balf.f. have significant cytotoxicity especially for breast cancer cell lines. Further studies are required for the isolation of constituents and to explore the mechanism of action.